Frequency of Etiological Factors Involved in patient of Epistaxis presenting at D.G Khan Hospital, D.G Khan - Muhammad Wahid Saleem, Ghulam Dastgir Khan, Ashfaq Hussain, Muhammad Farooq Bhutta, Muhammad Afzal, Rao Ammar Nasir (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To determine the frequency of etiological factors involved in patient of epistaxis presenting at D.G Khan Hospital, D.G Khan. Study design: Cross sectional study Place and duration: Department of ENT, D.G Khan Hospital, D.G Khan from January 2022 to September 2022. Methodology: Total 167 patients with acute episode of nasal bleeding, either male or female, age between 10-60 years were recruited and etiological factors of episode were evaluated. Results: Total 167 patients with Epistaxis were selected. Mean age was 39.03 ± 14.97 years. Age range was 10-60 years, Males were 103 (62%) while females were 64 (38%). The commonest cause of epistaxis was idiopathic 86 (51.5%) cases, followed by nasal trauma 39 (23.4%), Nasopharyngeal carcinoma 11 (6.6%), sinusitis 9 (5.4%), tumors 5 (3%) bleeding disorder 8 (4.8%) and hypertension in 9 (5.4%) patients. Practical implication: Understanding the frequency of etiological factors involved in patients with epistaxis is a critical objective. The practical implications of this research could have significant benefits for the community: Improved Clinical Practice: By determining the common causes of epistaxis, healthcare professionals can improve their diagnostic approach, providing more accurate and timely treatment, ultimately leading to better patient outcomes. Early Intervention and Prevention: Understanding the etiological factors may enable the development of preventative strategies or early intervention approaches, potentially reducing the overall incidence of epistaxis. Education and Awareness: This study could lead to increased public awareness about the common causes of epistaxis, encouraging individuals to take necessary precautions and seek early medical attention when needed. Resource Allocation: Health resources could be better distributed based on the findings of this study, ensuring that facilities and personnel are adequately equipped to handle the most common causes of epistaxis. Overall, this study could substantially contribute to the community's overall health by enhancing the management and understanding of epistaxis. Conclusion: Results was present study showed that most common etiological factor of epistaxis was Idiopathic and nasal trauma was second in number. In most of cases, right nasal cavity was involved. Male were more victim of epistaxis as compared to females and epistaxis was commonly seen in 4th and 5th decade of life. Keywords: Epistaxis, Nosebleed, Idiopathic, etiology, nasal tumor, hypertension, nosebleed